2014
DOI: 10.1002/hbm.22539
|View full text |Cite
|
Sign up to set email alerts
|

Hypoactivation in right inferior frontal cortex is specifically associated with motor response inhibition in adult ADHD

Abstract: Adult ADHD has been linked to impaired motor response inhibition and reduced associated activation in the right inferior frontal cortex (IFC). However, it is unclear whether abnormal inferior frontal activation in adult ADHD is specifically related to a response inhibition deficit or reflects a more general deficit in attentional processing. Using functional magnetic resonance imaging, we tested a group of 19 ADHD patients with no comorbidities and a group of 19 healthy control volunteers on a modified go/no-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 64 publications
5
44
0
Order By: Relevance
“…We reported that MPH normalized the hemodynamic responses in the right middle and inferior gyri during a motor-related inhibitory task (go/no-go task) using fNIRS on young ADHD children (Monden et al, 2012b), which was in accordance with previous evidence from a study with adult ADHD patients and fMRI (Morein-Zamir et al, 2014). …”
Section: Introductionsupporting
confidence: 89%
“…We reported that MPH normalized the hemodynamic responses in the right middle and inferior gyri during a motor-related inhibitory task (go/no-go task) using fNIRS on young ADHD children (Monden et al, 2012b), which was in accordance with previous evidence from a study with adult ADHD patients and fMRI (Morein-Zamir et al, 2014). …”
Section: Introductionsupporting
confidence: 89%
“…Figure 1 shows the PRISMA flow chart (44) of the selected studies. Including the 16 previously included datasets (1012;4557) from (6), we retained a total of 26 datasets (1013;3543;4557) for qualitative synthesis and 24 datasets (1013;3538;40;41;43;4557) for meta-analysis [two studies (39;42) did not report coordinates that could be entered into meta-analyses]. The Supplement lists the studies from the updated search that were not included in the meta-analysis, with reasons for their non-inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…As the meta-analysis of ADHD-related hyperactivated regions would have been underpowered (24), we did not run it. Excluding two studies (39;42) reporting no significant contrasts between adults with ADHD and controls, we found a total of 12 papers including tasks exploring inhibition (1013;35;40;41;45;47;48;50;52) (reporting, overall, 10 contrasts “Controls > ADHD” and 6 contrasts “ADHD > Controls”), six including working memory tasks (37;46;51;54;56;57), six focusing on attention tests (40;41;4750), five assessing reward processes (35;36;42;43;49;53), one using the instructed fear test (38) and one based on the paced/unpaced finger tapping test (55). Therefore, we did not perform planned sub-group analyses based on task type because the number of contrasts was substantially less than 15 (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for functional changes, patients with ADHD have been shown to have abnormal activity in the orbitofrontal, middle temporal, and dorsolateral prefrontal cortex (Fig 4). Hypoactivation in the inferior frontal cortex in patients with ADHD has been related to impaired behavioral response inhibition, which is a central neurobehavioral feature of ADHD (78). Hyperactivation in the striatum and mediotemporal areas during working memory tasks suggests that atypical corticostriatal circuitry may be an important component in the pathyphysiology of ADHD (7).…”
Section: State Of the Art: Psychoradiologymentioning
confidence: 99%